Stacking gels: A method for maximising output for pulsed-field gel electrophoresis - Heng, S.K.; Heng, C.K.; Puthucheary, S.D. (Medknow Publications, 2009)
Pulsed field gel electrophoresis (PFGE), the gold standard of molecular typing methods, has a major disadvantage of an unusually long electrophoretic time. From the original protocol of 6 days, it was modified to 3 days and subsequently to a single day. We describe the procedure of stacking five to six gels one on top of another in order to increase and maximize the output in a shorter time without compromising the resolution and reproducibility. All the variables that affect pulsed field gels during electrophoresis were taken into consideration. We firstly optimized the parameters to be used and secondly determined whether stacking of five to six gels had any effect on the molecular separation during electrophoresis in comparison with a single gel run. DNA preparation, restriction, electrophoresis, staining and gel documentation was carried out based on previously published methods. Gels were analysed using BioNumerics and dice coefficient and unweighted pair group methods were used to generate dendrograms based on 1.5% tolerance values. Identical band profiles and band resolution-separation were seen in the PFGE patterns with single gel and multiple stacking gels. Cluster analysis further strengthened the fact that results from stacking gels were reproducible and comparable with a single gel run. This method of stacking gels saves time and maximizes the output at the same time. The run time for a single gel was about 28 hours, but with six stacked gels the run time was 54 hours compared with 28 x 6 = 168 hours if they were run separately as single gels thus saving time of 67.86%. Beside the big factor of saving time, stacking gels save resources (electricity, reagents, water, chemicals and working time) by increasing the sample throughput in a shorter time without compromising on quality of data. But optimization of working parameters is vital depending on the PFGE system used.